2016
DOI: 10.1007/s00381-016-3180-5
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative neurophysiological mapping and monitoring during brain tumour surgery in children: an update

Abstract: Intra-operative neurophysiology is the gold standard to localise and preserve brain functions during surgery and is increasingly used in paediatric neurosurgery. Yet, the developing nervous system has peculiar characteristics in terms of anatomical and physiological maturation, and some technical aspects need to be tailored for its use in children, especially in infants. This paper will review the most recent advances in the field of intra-operative neurophysiology (ION) techniques during brain surgery, focuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Schucht et al [28] in their series of 8 pediatric patients with 4 preadolescents found that the quantitative mapping thresholds for assessing the risk of direct damage to the motor cortex were similar to the established values found in adults [26]. Thus, the recent modifications in the technique of mapping and monitoring strategies in preadolescents have established it as reliable and safe as in adults [4, 25, 29, 30].…”
Section: Discussionmentioning
confidence: 93%
“…Schucht et al [28] in their series of 8 pediatric patients with 4 preadolescents found that the quantitative mapping thresholds for assessing the risk of direct damage to the motor cortex were similar to the established values found in adults [26]. Thus, the recent modifications in the technique of mapping and monitoring strategies in preadolescents have established it as reliable and safe as in adults [4, 25, 29, 30].…”
Section: Discussionmentioning
confidence: 93%
“…Though limited, experience with high-frequency monopolar stimulation in pediatric cases has shown that it is safe and feasible and can be reliably used when coupled with other complementary techniques such as phase reversal. [ 3 ] During resection of tumors around the central motor areas, besides mapping the cortex, it is extremely important to preserve the descending fibers of the corticospinal tract. Subcortical mapping is therefore very crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative neurophysiological mapping and monitoring techniques have evolved in the last decade and provide a valuable means of assessing the functional status and thereby guide the resection even in pediatric cases. [ 3 ] Motor mapping (both cortical and subcortical) is one such very reliable technique. Recently, a new technique for continuous and dynamic subcortical mapping was described in adults using a suction monopolar stimulator device.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromonitoring intraoperatively is considered to be the gold standard in localizing brain function in brain tumor surgery ( 40 ). Mapping is the process of identifying the proximity to eloquent areas in the brain and avoiding damage to these regions ( 41 ).…”
Section: Operative Interventionmentioning
confidence: 99%
“…Though there is sufficient evidence to support the use of ION in predicting neurological injury, there isn't much evidence for injury prevention ( 40 ).…”
Section: Operative Interventionmentioning
confidence: 99%